Business Plan - Kantor, Tomasz; Pernica, Karel; Honcová, Martina; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
The goal of this thesis is to create a detailed business plan for the startup idea. The company is focused on the harmful effect of social media and argues the business to be the best current solution to the problem. The first part of the thesis consists of thorough descriptions of components of a successful business plan, and following sections bring the theory into the practice. One of the objectives of the plan is the validation of the business idea. In the strategic section are commonly used frameworks and analyses for the evaluation of the market and company’s competitive advantage. Scenario planning based on two uncertainties deals with the potential financial crisis and its impact on the company. Second, to last is an original marketing plan which combines traditional marketing practices and modern ways which often take advantage of the latest technology trends. Finally, the financial plan which projects cash flow three years to the future and finds the profitable business model.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses